Reconstruction of Criminal Responsibility of Road Users for the Impact of Psychological Trauma on Witnesses and Indirect Victims of Traffic Accidents - Andi Suprapto; Suparno (Journal Customary Law, 2026)
This article examines the construction of criminal liability for road users in Indonesian traffic law, which to date still focuses on physical consequences and material losses, while the impact of psychological trauma experienced by witnesses and indirect victims of accidents has not yet been recognized as a relevant legal consequence. Social reality shows that traffic accidents not only cause bodily injury or property damage, but also psychological suffering in the form of post-traumatic stress disorder, anxiety, and other mental disorders that seriously impact the quality of life. This study aims to analyze the weaknesses in the regulation of criminal liability for road users in positive law and to formulate a model for reconstructing criminal liability that is more responsive to psychological trauma. The method used is normative legal research through a statutory and conceptual approach by examining criminal law doctrine, victimology, forensic psychology, and the principles of substantive justice and human rights. The results of the study indicate that psychological trauma deserves to be positioned as a conceptually legitimate consequence of crime, accompanied by the recognition of witnesses and indirect victims as subjects of legal protection. Therefore, the reconstruction of criminal liability for road users needs to be directed at integrating punishment and psychological recovery to create a more humane, proportional, and just traffic law system.